Conceptual design of a space nuclear fast reactor - Josef Sabol; Jan Frýbort (Acta Polytechnica)
This paper finds an improved combination of fuel, enrichment, and coolant for a fast reactor suitable for nuclear electric propulsion. The study simulates an infinite lattice considering two enrichments, with fuel options (ceramics and metal alloys), and with alkali metals as a coolant. Following this, a simplified core model is developed to ensure long-term reactivity control and safe shutdown at a thermal power of 10 MW for 10 years, focusing on minimising size and mass. The findings indicate two viable fuel and coolant combinations, depending on temperature requirements. For temperatures up to 1 100 K, the U-10Zr and Na combination is preferable due to its smaller critical dimensions and reduced mass. For higher temperatures, up to 1 550 K, the UN and Li combination is suitable. The choice of operating temperature is critical, as heat rejection in space depends only on radiation, covered by the Stefan-Boltzmann law, where heat flux depends on the fourth power of the temperature.